Serum matters: human platelet lysate enables physiological modeling of HIV-1 infection in dendritic cells - Schweighofer, Paul; Erlacher, Magdalena; Posch, Wilfried; Wilflingseder, Doris (Frontiers in Immunology, 2025)
Monocyte-derived Dendritic Cells (moDC) are fundamentally involved in infectious processes and serve as model cell type for studying immune regulatory functions in vitro. How DCs behave in viral infections is influenced by various intra- and extracellular factors. Thus, working as physiologically as possible is crucially important for gaining mechanistic insights. We and others previously stressed a critical role of DCs in the course and transmission of human immunodeficiency virus (HIV) infection. Up to date, moDCs are differentiated in presence of FCS-based media, comprising undefined factors that might impact cell differentiation behavior and function. While a few studies addressed working under xeno-free conditions enhancing reproducibility and clinical applicability, differences between FCS and hPL-generated DCs with respect to infection disease processes remain poorly defined. In this study we established an animal component-free protocol to induce primary moDCs, and systematically compared FCS stimulated DCs versus hPL-induced DCs phenotypically and functionally. Our data revealed, that hPL shows high differentiation potential and infection potency of DCs by complement-opsonized HIV-1 (HIV-C). All in all, we established an animal component-free in vitro model to generate primary CD11c+CD209+-moDCs by use of hPL, which is a valuable tool to study viral infections and interactions in vitro and under more defined conditions compared to FCS-generated DCs.